A rare cause for delirium: COPE syndrome - Anandan, Somarajan; S Rajendran, Sajeesh; P Kumar, Jyothish; S Shajee, Divine (Indian Journal of Case Reports, 2024)
Calcium-alkali syndrome (CAS) (Milk alkali syndrome) is the third most common cause of hypercalcemia. The triad of hypercalcemia, metabolic alkalosis, and variable renal failure constitutes this syndrome. Here, we report a case of CAS in a female with post-thyroidectomy hypoparathyroidism who presented with delirium due to hypercalcemic encephalopathy. CAS can occur even after decades of normocalcemia in hypoparathyroidism, and regular monitoring of calcium levels is required.